Licochalcone D mitigates intracerebral hemorrhage-induced ferroptosis of neurons through COX2 inhibition - Song, JiaLi; Qiao, HuiYing; Dong, ShunLi; Tang, JingMei; Li, Bai; Zhou, Xi; Lv, Shan; Lv, Rong (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to assess LCD’s neuroprotective pharmacological effects against SBI post-ICH and identify its ferroptosis-inhibiting targets.MethodsAnimal models of ICH and cellular models of SBI were established. Subsequently, gradient concentrations of LCD were administered at both the animal and cellular/molecular levels. The extent of ICH injury was evaluated using a range of methods, including CCK8 assay, Flow Cytometry, quantification of CAT and MDA, CI staining, Western blot, and HE staining. The SWISS TARGET prediction tool and molecular docking were utilized to confirm LCD’s target pathway and its binding site on COX2. Quantification of ferroptosis-executing proteins, BODIPY ROS staining, quantification of PGE2, MDA, and CAT were observed to assess the pharmacological effects, trends in ferroptosis influence, and to elucidate the underlying pathway mechanism.ResultsPretreatment with LCD can improve the state of SBI before the induction of an ICH model. Compound target prediction analysis revealed 102 differentially expressed genes (p < 0.05) associated with the drug target of LCD, with COX2 exhibiting the most significant expression. Furthermore, we found that LCD intervention suppressed COX2 expression, and pretreatment with COX2 overexpression in the ICH model group negated the pharmacological effects, of LCD on neuronal cell ferroptosis and SBI. It is proposed that by targeting COX2 through early LCD administration in ICH, ferroptosis in nerve cells can be reduced and SBI outcomes can be improved. To further elucidate the mechanism of targeting COX2, we found that PGE2, a downstream metabolite of COX2, is also regulated by LCD. By screening its impacts on the EP receptor family (EP1, EP2, EP3, EP4), it was found that COX2 is specifically targeted and suppressed by LCD pretreatment prior to ICH modeling, which further inhibits the PGE2/EP1 pathway, thereby reducing ferroptosis-specific lipid peroxidation.ConclusionLCD pretreatment reduces ferroptosis in neurons and alleviates SBI after ICH by blocking the COX2/PGE2/EP1 pathway. Early LCD use may improve SBI, highlighting its potential as a pharmacological option for ICH outcomes.